(untitled) (REMUNOM, 2025)
Abstract Leprosy is an infectious and chronic disease caused by the bacillus Mycobacterium lepraeou Hansen. It compromises the skin, mucous membranes and peripheral nervous system. The severity of the disease is not only assessed by the number of existing patients, or by its contagiousness, but by the disabilities it produces, psychosocial problems and the long duration of treatment. Since ancient times, leprosy has been considered a contagious, mutilating and incurable disease, causing a prejudiced attitude of exclusion and discrimination towards its sufferer, normally an outcast in society. According to a study developed in 2012 by Paloma Benigno Morais (2012), the municipality of Teófilo Otoni - MG was considered endemic and few control actions were related. This article is research based on a cross-sectional and observational, qualitative and quantitative analysis of data provided by the Municipal Health Department with the aim of verifying whether the disease is expanding or heading towards suppression. The result of the research demonstrates that the city no longer has a super-endemic profile, as the number of cases identified was 0.057% of cases between 2017 and 27/09/2022. The dissemination of awareness and prevention campaigns are essential for controlling and monitoring the disease. Keywords:Leprosy; Epidemiological Profile; Diagnosis; Treatment.